A formative evaluation of the implementation process of the supply chain management policy framework in Eastern Cape Provincial Administration - Sandler, Jeanette Louise (Rhodes University, Faculty of Commerce, Rhodes Business School, 2011)
The Eastern Cape Provincial Administration has, since the promulgation of the Supply Chain Management Policy Framework in 2003, been challenged with the implementation of the said Policy.Some departments have progressed better than others, but all of the provincial departments have been challenged in one way or another.It was therefore, necessary to research the reasons for the erratic implementation process by the different departments. An analysis, based on answers provided by senior officials of the Eastern Cape Provincial Administration in an interviewing process, was needed to get an understanding of the challenges the departments are faced within the implementation process. In order to provide quality goods and services, this dissertation aims to evaluate the implementation process, provide insight to the challenges that the departments are faced with and offer recommendations on how to remedy these challenges. The lessons learned from this research study will assist the provincial departments to re-engineer their implementation processes and move forward to greater success and embracement of the Supply Chain Management policy Framework.
Keywords: Business logistics -- Management -- South Africa -- Eastern Cape; Public administration -- South Africa -- Eastern Cape; Materials management -- South Africa -- Eastern Cape; Industrial procurement -- Management -- South Africa -- Eastern Cape; Administrative law -- South Africa -- Eastern Cape